Numerical model of multiple sound scattering from gas bubbles in the sea - SZCZUCKA, J. (Archives of Acoustics, 1995)
This paper presents a model of sound scattering on gas bubbles aggregations in water. Coherence and second order scattering effects are taken into account for random and regular 3-dimensional distributions of bubbles with different parameters like bubble size, average separation between scatterers, distance to the receiver, incident sound frequency. Results of calculations for various sets of parameters are compared. Excess attenuation is also considered.